Pengaruh Mahasiswa Kampus Mengajar Angkatan Ke-6 Pada Pengembangan Keterampilan Pembelajaran Di SDN Kalangsemanding Jombang - La Masihu Tehuayo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to evaluate the impact of student participation in the campus teaching program 6th generation on the learning process carried out at SDN Kalangsemanding in the subjects of Mathematics, Science, Indonesian. The focus of this research is to identify the impact of the contribution of campus teaching program students 6 to the development of students' learning skills at the elementary school level. The research methods used in this study involve direct observation, interviews, and data analysis to measure improvements in learning skills in the classroom, social interactions with teachers and friends, as well as the positive or negative impacts of this program. The results of the research are expected to provide insight into the effectiveness of campus student participation in teaching 6 in improving the quality of learning in elementary schools. Students can feel inspired by seeing younger students who already have the knowledge and skills they want. The presence of campus students teaching at target schools can motivate students to pursue higher education and pursue their dreams. Students who may initially have difficulty connecting with teachers can still find a stronger connection or identification with younger campus teaching students and a less large age difference can create a better and more interesting learning environment. They were very happy with the presence of students at school, until the time for goodbye arrived, they were not willing to let campus students go to their respective campuses to teach.